1996
DOI: 10.1017/s0022377800019401
|View full text |Cite
|
Sign up to set email alerts
|

The theory of nonlinear ion-acoustic waves revisited

Abstract: The basic set of equations describing nonlinear ion-acoustic waves in a cold collisionless plasma, in the limit of long wavelengths, is reconsidered. First, a travelling-wave solution is found up to third order by means of a straightforward perturbation approach based on the smallness of the wavenumber. As a result, a positive dressed solitary wave shows up, which is larger, taller and faster than the KdV soliton, the first-order result. Furthermore, the accuracy of this approach is tested and compared with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 13 publications
7
41
1
Order By: Relevance
“…It is shown that the wave speed corresponding to the lowest order time parameter r gives the wave speed of the classical perturbation expansion, whereas the wave speeds corresponding to higher order time parameters give the speed corrections terms. The results obtained here are exactly the same as those given in Malfliet and Wieers [6] and Demiray [7],…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is shown that the wave speed corresponding to the lowest order time parameter r gives the wave speed of the classical perturbation expansion, whereas the wave speeds corresponding to higher order time parameters give the speed corrections terms. The results obtained here are exactly the same as those given in Malfliet and Wieers [6] and Demiray [7],…”
Section: Introductionsupporting
confidence: 90%
“…This requirement made it possible to remove the secularities that might occur and to determine the higher order correction terms to the wave speed. The result obtained in [7] was found to be in complete agreement with that of Malfliet and Wieers [6].…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…For this type of problems it is a common practice to use the hyperbolic tangent method [16]. For this we introduce a new variable η as η = tanh ζ and propose a solution of the form…”
Section: Longwave Approximationmentioning
confidence: 99%